O MST e a participação política dos camponeses sem terra : o caso do acampamento herdeiros da terra de Primeiro de Maio em Rio Bonito do Iguaçu/PR - Cezimbra , Elemar do Nascimento (2021)
This study aimed to verify the political participation of MST peasants in the Herdeiros da Terra de Primeiro de Maio camp in Rio Bonito do Iguaçu in the State of Paraná, which on May 1, 2014 occupy the property Pinhal Ralo, a landowner owned by the company Araupel. A questionnaire was applied to 70 peasants and a semi-open interview was conducted with 27 peasants and bibliographic consultations were carried out on works already carried out in the region with MST settlements and camps. The methodology has a participatory and interdisciplinary character, and the author participated in the fighting processes in the region and in the camp in question as a militant and leader of the MST. A theoretical approach was made on the channels of political participation of peasants in the spaces of the modern bourgeois state. Bibliographical research was also carried out on peasants and capitalism based on Marxist and non-Marxist authors. In another item, it was demonstrated how the struggles for land in the Center South region developed by peasants linked to the MST constituted a reformed region with many settlements that support the expansion of new occupations. Finally, it seeks to show how the participation of the peasants was concretely in the realization of the camp that inherited the land of May, in the occupation of the latifundium and in the pre-settlement, in the mobilizations, in the daily life of the camp and in the organization of education in the camp as a differential of the MST in relation to other peasant movements of the past.